Pengaruh Warna Bohlam Terhadap Nilai Radiasi Kalor - Akuba, Kisman R.; Paputungan, Devi Triana; Virna, Rila; Kurniasari, Septiana (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2024)
In daily activities, there is a phenomenon that is the opinion of the general public that people who wear black feel hotter than people who wear other colors. A bulb is an artificial light source that results from channeling an electric current through a filament which then heats up and produces light. This research aims to measure the heat radiation value of different colored bulbs. The method of this research is that several bulbs of different colors are measured for heat radiation at varying times of 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes and 30 minutes. The research results show that black has the largest temperature changes, and transparent colors have the smallest temperature changes compared to other colors. Dominantly dark colors are better conductors of heat.